Open reading frames E6 and E7 of bovine papillomavirus type 1 are both required for full transformation of mouse C127 cells. - Neary, K (1989)
A series of mutations in open reading frames (ORFs) E6 and E7 of bovine papillomavirus type 1 (BPV1) was constructed to analyze the roles of these ORFs in transformation of mouse C127 cells. The mutations were designed to prevent synthesis of specific proteins encoded by these genes. None of the mutations caused a decrease in the focus-forming activity of the full-length viral genome or in the ability of the viral DNA to replicate as a high-copy-number plasmid. Analysis of these mutants in the absence of a functional BPV1 E5 gene revealed a weak focus-forming activity encoded by ORF E6. Mutations preventing synthesis of the E6 protein did cause defects in anchorage-independent growth and tumorigenicity of transfected and transformed cells. However, a frameshift mutation between the first and second ATG codons of ORF E6 did not inhibit induction of colony formation, suggesting that translation from the first methionine codon is not required. Mutations that inactivated ORF E7 or E6/E7 individually did not inhibit induction of colony formation in agarose. However, a defect in this activity was caused by simultaneous disruption of both ORF E7 and ORF E6/E7 when they were expressed from the full-length viral genome but not when they were expressed under the control of a retrovirus long terminal repeat. These results suggest that translation of both ORF E6 and the 3' end of ORF E7 is required for efficient induction of anchorage-independent growth by the intact BPV1 genome.